2011
DOI: 10.1080/08911762.2011.592460
|View full text |Cite
|
Sign up to set email alerts
|

Brand Personality and Emotional Attitudes: The Case of Mobile Telephone Operators

Abstract: As part of a brand image, brand personality has aroused for years the interest of scholars and marketers. This article examines this concept in the case of two mobile telephone operators in Tunisia (North Africa). An empirical investigation, based on a sample of 272 students, has shown that brand personality influences and above all is influenced by emotional attitudes within consumers. At a managerial level, this study sheds light on the main brand personality traits (agreeableness, conscientiousness, sophist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
(44 reference statements)
0
5
0
2
Order By: Relevance
“…This present study, unlike previous research works on brand personality which was conducted in different context such the telecommunication industry (Klabi and Debabi, 2011), retailing (Das, 2014a, b), and automobile industry (Ha and Janda, 2014), combined both brand personality as well as functional congruity to test how consumers build loyalty towards automobile brands. Both aforesaid constructs play a pivotal role in building brand loyalty in the car industry, and most importantly in developing different loyalty stages.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…This present study, unlike previous research works on brand personality which was conducted in different context such the telecommunication industry (Klabi and Debabi, 2011), retailing (Das, 2014a, b), and automobile industry (Ha and Janda, 2014), combined both brand personality as well as functional congruity to test how consumers build loyalty towards automobile brands. Both aforesaid constructs play a pivotal role in building brand loyalty in the car industry, and most importantly in developing different loyalty stages.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…It has been admitted by scholars and practitioners that BP can be used as a strategy for product differentiation as it results in brand preference, greater emotional bound to brand and loyalty (Klabi & Debabi, 2011). Besides, previous studies have also identified that BP is a good predictor of perceived product quality (Ramaseshan & Tsao, 2007), brand associations (Freling & Forbes, 2005a), brand trust (Klabi & Debabi, 2011), brand commitment (Eisend & Stokburger-Sauer, 2013) and purchase intention (Ha & Janda, 2014). Therefore, on this basis, we can assume that if BP can influence consumers to develop brand preference, trust, positive product quality evaluation, purchase intention as well as loyalty and commitment, it would make sense to consider that there would be a negative relationship between BP and consumer switching behaviour.…”
Section: Brand Personalitymentioning
confidence: 99%
“…The population for this study was consumers of the Nigerian telecommunication industry resident in Lagos State, which is a melting pot of all the Nigerian cultures due to its designation as Nigeria's economic focal point (About Lagos, n.d.). Klabi and Debabi (2011) as well as Čáslavová and Petráčková (2011) supported this category of subjects. In line with Aaker's (1997) use of non-probabilistic volunteer sampling 700 volunteers who were all students of the University of Lagos Distance Learning Institute completed copies of the questionnaire.…”
Section: Population and Samplingmentioning
confidence: 71%